2017
DOI: 10.3390/informatics4020010
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Opportunities to Integrate Digital Professionalism into Curriculum: A Comparison of Social Media Use by Health Profession Students at an Australian University in 2013 and 2016

Abstract: Social media has become ubiquitous to modern life. Consequently, embedding digital professionalism into undergraduate health profession courses is now imperative and augmenting learning and teaching with mobile technology and social media on and off campus is a current curriculum focus. The aim of this study was to explore whether patterns of social media use for personal or informal learning by undergraduate health profession students enrolled at an Australian university across four campuses has changed over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Nursing students used digital devices such as computers, laptops, iPads, iPods, and Smartphones to communicate, access educational applications, and learning materials in the face to face classes, virtual classes and clinical laboratories ( Brown & McCrorie, 2015a ; Ferguson et al, 2016 ; Mawson, 2014 ). Furthermore, these devices enabled students to communicate and collaborate with their peers and the faculty through social media platforms such as Facebook, Skype, Twitter, and YouTube ( Bogossian et al, 2018 ; Ferguson et al, 2016 ; Mather, Douglas, & Jane, 2017 ). Social media facilitated safe collaboration, independent learning, access to resources, and collaboration during group work and assignments ( Ferguson et al, 2016 ; Mather et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nursing students used digital devices such as computers, laptops, iPads, iPods, and Smartphones to communicate, access educational applications, and learning materials in the face to face classes, virtual classes and clinical laboratories ( Brown & McCrorie, 2015a ; Ferguson et al, 2016 ; Mawson, 2014 ). Furthermore, these devices enabled students to communicate and collaborate with their peers and the faculty through social media platforms such as Facebook, Skype, Twitter, and YouTube ( Bogossian et al, 2018 ; Ferguson et al, 2016 ; Mather, Douglas, & Jane, 2017 ). Social media facilitated safe collaboration, independent learning, access to resources, and collaboration during group work and assignments ( Ferguson et al, 2016 ; Mather et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, these devices enabled students to communicate and collaborate with their peers and the faculty through social media platforms such as Facebook, Skype, Twitter, and YouTube ( Bogossian et al, 2018 ; Ferguson et al, 2016 ; Mather, Douglas, & Jane, 2017 ). Social media facilitated safe collaboration, independent learning, access to resources, and collaboration during group work and assignments ( Ferguson et al, 2016 ; Mather et al, 2017 ). Students used social media, journals, television, and radio as sources of information ( Mather et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a study measuring students’ perceptions of the usefulness and ease of use of technology as a pedagogical tool in nursing education showed that they saw it as highly useful. In addition, use of social media in nursing education attracts interest as a learning platform [53-55] but is not seen as uncontroversial despite the potential benefits [56].…”
Section: Introductionmentioning
confidence: 99%